KESANTUNAN DALAM TINDAK TUTUR MEMERINTAH ANAK USIA SEKOLAH DASAR DAN IMPLIKASINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Candra Pratiwi; nurlaksana eko rusminto; ni nyoman wetty (FKIP Universitas Lampung, 2013)
This research is conducted to determine modesty which is used by children whose ten years on elementary school. The purpose of this research to describe modesty in a speech act ruled a school age child base and the implication of Indonesian learning. This research used descriptive qualitative design. The data source of this research was a ten years boy who is in elementary school. The data of this research was in modesty of a speech act ruled by the subject. The result show the modesty of a speech act by the child in form of speech, was namely direct speech and indirect speech. Modesty in direct speech immediately was done by five ways, that is a direct command order by linguist, command of request, command of supply, orders conditional, and direct orders with the argument. The modesty indirect command doing by special way which was called mode. There were nine modes which were found in this research, namely declare inability, inform, declare fact, supposition, game, complain, involving the third person, ask, and refusal. The son use context, namely place, time, the third people, events, and the weather. Beside that, the son also used of markers modesty “tolong”, “dek”, and “kita”. This research result can be information for the elementary Indonesian teacher to know development of children language as well as to learn the speech act of the children and modesty of in a speech act that son doing.Key words : modesty, speech act, command, mode, context